Uji Kualitas Telur Cacing STH Menggunakan Pewarna Alami Perasan Daun Jati (Tectona grandis) dengan Konsentrasi 40%, 60%, 80%, 100% sebagai Pewarna Alternatif Metode Sedimentasi - Anggraini, Maysita Ari; Afrianti, Dina (Poltekkes Kemenkes Semarang, 2024)
Helminthiasis is a parasitic infection in the form of worm larvae or eggs that develop in the human body. Diagnosing helminthiasis with fecal examination uses 2% eosin dye to clarify and emphasize the shape of worm eggs. Eosin 2% is a class-3 IARC carcinogenic reagent, so a natural reagent that does not damage the environment is needed. Reagents from natural materials that can be utilized are teak leaves containing anthocyanin compounds that can clarify and emphasize the shape of worm eggs. The purpose of this study was to determine the quality of sth (soil transmitted helminth) worm eggs using natural dye teak leaf juice (tectona grandis) with a concentration of 40%, 60%, 80%, 100% as an alternative dye sedimentation method. The design of this study is quantitative with experimental design with posttest with control group design with Kruskal-Walis test. The results of this study obtained the concentration with the highest average value, namely 40% concentration of 8.7. The higher the concentration, the less clear the morphology of the egg because of the influence of dirt / residue from the juice. The results of the Kruskal-Walis test sig value 0.054, it can be concluded that there is no difference between teak leaf juice with a concentration of 40%, 60%, 80%, and 100% with 2% eosin dye as a control. Based on the mean rank value of the Kruskal-Walis test, it can be seen that the best teak leaf juice concentration is 40% concentration with a value of 34.50. This research can be used as a reference for the utilization of teak leaves as a natural dye to replace 2% eosin for STH worm eggs.